Medicinal and Aromatic Plants as Hosts of Natural Enemies of Saissetia Oleae in Spatio-Temporal Arrangements for the Agroecological Cultivation of Olea Europea [Plantas Medicinales y Aromáticas Como Hospederas de Enemigos Naturales de Saissetia Oleae en Arreglos Espacio-Temporales Para el Cultivo Agroecológico de Olea Europea] - Martinez-Salinas, J; Peredo-Parada, S; Barrera-Salas, C (Universidad de Santiago de Chile, 2020)
Medicinal and aromatic plants can be considered as “multifunctional plants” due to the diverse properties and ecosystem servi ces they provide in agroecosystems. Among the latter, they regulate the populations of insect pests in crops, harboring their nat ural enemies. In order to determine the plant species with the greatest presence of natural enemies of Saissetia oleae in an agro-ecological crop of Olea europea, biological corridors with species of medicinal and aromatic plants were established in three sectors of the farm. The plant s were collected together with the farmers of the Maipo Province and sticky pheromone traps, vacuum cleaner and entomological umbrella were used to collect the arthropods. The results indicate that Calendula officinalis, Borago officinalis, Aquilea millefolium, Linun usitatissimun, Chamaemulum nobile, Origanum vulgare, Artemisia agrotanum and Symphytum officinale are the species with the highest presence of S. oleae natural enemies identified as Coccophagus sp., Metaphycus helvolus, Metaphycus lounsbury, Metaphycus sp., Rhyzobius lophanthae, Scutellista caerulea. © 2020, Universidad de Santiago de Chile. All rights reserved.